Immunoglobulin G4-related disease - diagnostic dilemma and importance of clinical judgement: a case report - Chandrasekaran, Jagadeesh; Machiraju, Phani Krishna (International Journal of Research in Medical Sciences, 2020)
Immunoglobulin G4 (IgG4)-related disease is a multi-organ, immune-mediated, fibro-inflammatory disorder characterized by tumefactive masses in the affected organs. Incidence and prevalence of IgG4-related disease (RD) are not clearly known and have slight male preponderance. It often involves multiple organs at the time of presentation or over the course of disease mimicking malignancy, Sjogren's syndrome, antineutrophil cytoplasmic antibodies associated vasculitis, infections. A thorough workup is needed to rule out these mimickers. A 33-year-old gentleman presented to us with history of progressive swelling in the right peri-orbital region for four years. On evaluation, abdominal imaging was notable for the sausage-shaped pancreas and hypoenchancing nodules in bilateral kidneys. Histological examination of right lacrimal gland revealed lymphoplasmacytic infiltrate and storiform fibrosis. Serum IgG4 levels were normal, and immunostaining was negative. A diagnosis of IgG4-RD was suggested because of multi-organ involvement, classical radiological and histopathological features. Awareness about IgG4-RD, an under-recognized entity is essential, as it is treatable, and early recognition may help in a favourable outcome. Appropriate use of clinicopathological, serological and imaging features in the right clinical context may help in accurate diagnosis. Elevated serum IgG4 levels and biopsy are not mandatory for the diagnosis.